Systemic Lupus Erythematosus and DNA Degradation and Elimination Defects - Arneth, Borros (Frontiers in Immunology, 2019)
Introduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that is characterized by the production of autoantibodies specific for components of the cell nucleus and that causes damage to body tissues and organs. The pathogenesis of SLE remains unclear, with numerous studies pointing to a combination of genetic and environmental factors. A critical stage in SLE development is cell necrosis, in which undegraded chromatin and nucleoproteins are released into the blood, resulting in circulating cell-free DNA and serum nucleoproteins that trigger anti-dsDNA autoantibody production. This systematic literature review aimed to examine whether SLE stems from a DNA degradation and elimination defect. Materials and Methods: An advanced literature search was conducted in PubMed using the following keywords: [(“SLE” OR “Systemic Lupus Erythematosus” OR “Lupus”)] AND [(“DNA” OR “DNA Degradation”)] AND [(“Defect Elimination”)]. More articles were obtained from the references of the identified articles and basic Google searches. Twenty-five peer-reviewed articles published within the past 10 years (2007–2018) were included for review. Results: The findings of each study are summarized in Tables 1, 2. Discussion and Conclusion: The etiopathogenesis of SLE remains controversial, which limits therapeutic inventions for this disease. However, SLE is a DNA degradation and elimination disorder caused by uncleared histones and nuclear material that leak into the extracellular space and form cell-free DNA, triggering an immune response that destroys tissues and organs. Under normal conditions, apoptosis allows DNA and other nuclear material to be efficiently cleared through degradation and additional complex mechanisms such that this material does not trigger the immune system to produce nuclear autoantibodies.